The relationship between family functioning and religiosity on readiness for change among persons under surveillance - Shahrom, Siti Hazreen; Hassan, Siti Aishah; Engku Kamarudin, Engku Mardiah (Canadian Center of Science and Education, 2021)
There are numerous theoretical perspectives on addiction and the behavioural change processes during the transition from addiction to recovery. Although the precise nature of the relationship between religion and family function has not been discovered, it has been highlighted as a significant component in addiction. This study examines the relationship of family functioning and religiosity on the readiness for change among Persons under Surveillance (PuS). We randomly selected respondents (n = 85) of PuS in the National Anti-Drugs Agency (NADA), Jempol District, Negeri Sembilan, Malaysia, who participated in this study. Descriptive analysis was used to identify the level of family functionality, religiosity and readiness for change. Next, Pearson correlations were used to determine the relationship of family functionality to change and religiosity to the readiness for change. Findings showed a significant correlation (p = 0.00, p <0.05) between family functioning and readiness for change and it was a low positive correlation (r = +0.47). Moreover, findings showed a significant correlation (p = 0.01, p <0.05) between religiosity and readiness to change the relationship was a weak positive correlation (r = + 0.27). In conclusion, family functioning and religiosity are related to readiness for change. This relationship is significant for PuS in NADA Jempol to implement self-care and for the divisional staff involved in NADA Jempol to develop prevention and rehabilitation strategies to prepare PuS out of the drug problem.